Orthogonal Analysis of Flexural Capacity of Beams Reinforced by High-strength Bar and Ultra High Performance Concrete with Coarse Aggregate - TANG Jiajun; AN Silong; HU Jie; WANG Tan; LI Jiuyang (Renmin Zhujiang)
In order to study the influencing factors of the flexural capacity of beams reinforced by high-strength bar and ultra high performance concrete with coarse aggregate (UHPC-CA),this paper analyzes the influence of bar grade,bar diameter,effective section height and concrete strength grade on the flexural capacity of beams reinforced by high-strength bar and UHPC-CA by the orthogonal test method.The results show that:The bar diameter is an important significant factor affecting the flexural capacity of beams reinforced by high-strength bar and UHPC-CA,and the bar grade and the effective section height are general significant factors.With the increase of the three factors,the flexural capacity of beams is gradually improved.The influence of concrete strength grade on the flexural capacity of beams reinforced by high-strength bar and UHPC-CA is small.With the increase of concrete strength grade,the flexural capacity first decreases slightly and then increases slightly.The impact of reinforcement ratio on flexural capacity of beams reinforced by ordinary-strength bar and UHPC-CA is greater than that of beams reinforced by high-strength bar and UHPC-CA.